Effect of Chemical Grafting Parameters on the Manufacture of Functionalized PVOH Films Having Controlled Water Solubility - Haas, Andreas; Schlemmer, Daniel; Grupa, Uwe; Schmid, Markus (Frontiers in Chemistry, 2017)
This study investigated the chemical grafting of a single-layer poly(vinyl alcohol) (PVOH) film. The effect of the grafting parameters (grafting time, grafting temperature, and concentration of fatty acid chloride) on the hydrophobicity of the film surface and the film solubility were evaluated. The PVOH substrate film (cold-water soluble at 20°C) was manufactured by flat extrusion and had a thickness of 50 µm (± 5 µm). The chemical grafting was performed using the transfer method with palmitoyl chloride (C16). The solubility, surface energy, and water vapor transmission rate of the grafted films were measured. The process parameters which produced the most hydrophobic PVOH film were found to be a fatty acid concentration of 3%, a grafting time of 14 min, and a grafting temperature of 130°C. These studies involved systematic adjustment of the hydrophobicity of one side of PVOH films. The results open up opportunities for packing fluids in water soluble packaging.